Romanje k "sveti smreki" na Paki pri Vitanju - Šmitek, Zmago (Traditiones (Ljubljana), 1999)
Since the pilgrimage to the "sacred spruce" at Paka by Vitanje in 1851 and 1852 was comparatively well documented it represents an important source for the understanding of Slovene folk religion. The ritual an important source for the understanding of Slovene folk religion. The ritual contains visible pre-Christian elements and shaws similarities with other European countries (the appearance of Our Lady on the tree, the healing brook in the vicinity, the tree with two or more tops, the bleeding of the wounded tree, punishment for culting down the tree, etc.)
Keywords: ethnology; etnologija; romanja